1970
DOI: 10.1111/j.1476-5381.1970.tb09909.x
|View full text |Cite
|
Sign up to set email alerts
|

The protective actions of some anticholinergic drugs in sarin poisoning

Abstract: Summary The central and peripheral anticholinergic activities of a series of drugs comprising atropine, hyoscine, caramiphen and one of its analogues, and three glycollic acid esters, have been measured. The ability of the same drugs used alone, and in conjunction with N‐methyl pyridinium‐2‐aldoxime methanesulphonate (P2S), to protect mice, rats and guinea‐pigs from the lethal effects of sarin has been assessed. No correlation was found to exist between central or peripheral anticholinergic activity and abili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

1984
1984
2012
2012

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(9 citation statements)
references
References 13 publications
1
8
0
Order By: Relevance
“…for subcutaneous administrations to rat, the LD 50s are 193 μg/kg for tabun, 103 μg/kg for sarin, 75 μg/kg for soman, and 12 μg/kg for VX (ref. [84][85][86] ). Median lethal concentration and time (LCt 50 ) in rats for sarin is 150 mg/m 3 for ten minutes lasting inhalation 87 .…”
Section: Fig 2 Inhibition Of Ache By Nerve Agent Sarin (Reaction 1)mentioning
confidence: 99%
“…for subcutaneous administrations to rat, the LD 50s are 193 μg/kg for tabun, 103 μg/kg for sarin, 75 μg/kg for soman, and 12 μg/kg for VX (ref. [84][85][86] ). Median lethal concentration and time (LCt 50 ) in rats for sarin is 150 mg/m 3 for ten minutes lasting inhalation 87 .…”
Section: Fig 2 Inhibition Of Ache By Nerve Agent Sarin (Reaction 1)mentioning
confidence: 99%
“…We fully agree with Ellin (1982) that guinea pigs respond differently from rats ("if subjected to combined pyridostigmine, atropine, and oxime therapy in organophosphate poisoning"). (Wills 1970) 0.07 (Sammet 1983) 0.4 (Lohs 1960) 0.42-0.59 (Wills 1970) 0.585 (Loomis 1956) 0.67 (Junod 1976) RATS 0.103 (Brimblecombe et al 1970) 0.045 (Ellin 1982) GUINEA PIGS 0.040 (Brimblecombe el al. 1970) 0.040 (Fonnum & Stern 1981) 0.060 (Lohs 1960) 0.060 (Wills 1970) 0.112 (own results) 0.034 Wills 1970 These aspects urgently support our call to put controls versus treated animals in a randomized sequence in all animal experiments with organophosphate poisoning.…”
Section: Discussionmentioning
confidence: 99%
“…As other authors (Lohs 1960;Wills 1970;Brimblecombe 1970;Fonnum & Sterri 1981) have reported lower doses to be effective, we injected our lowest dose (0.050 mg/kg) of sarin at two different times of the year. A first experiment with 6 guinea pigs on December 1982, was followed by a second experiment with the same number of animals on May, 1983.…”
Section: In Vivo Experimentsmentioning
confidence: 99%
“…Before the advent of carbamate prophylaxis, pralidoxime methanesulfonate tablets were issued to the British military. DeCandole and McPhaill, 1957Anderson et al, 1991Gupta and Dettbarn, 1992Brimblecombe et al, 1970Lundy et al, 1978Wolfe et al, 1987Berry et al, 1971Gordon et al, 1978 …”
Section: Prophylaxis Of Nerve Agent Poisoningmentioning
confidence: 96%